Bioactivity Test of Annona muricata, Chromolaena odorata, and Tinospora cordifolia extracts against Spodoptera frugiperda - R. Arif Malik Ramadhan; Efrin Firmansyah (Agrovigor, 2023)
The most strategy to control Spodoptera frugiperda in Indonesia is using synthetic pesticides. Synthetic pesticides for pests control are causing many negative effects. The use of biopesticide can be an environmentally friendly solution to control S. frugiperda. In line with the Vision and Mission of Universitas Perjuangan Tasikmalaya to develop local wisdom, it is necessary to study the potential of some local plants as vegetable pesticides against S. frugiperda. Result of field observations obtained three plants suspected of having potential as vegetable pesticide, including: Annona muricata, Chromolaena odorata, and Tinospora cordifolia. This study aims to test the bioactivity of the three plant extracts against larval mortality, antifeedants, and development inhibition of S. frugiperdalarvae. The test was carried out with the residue method on the feed withno-choice test. Each plant extract was tested with a concentration of 1%, 2%, 3%, and one control treatment. Each treatment used 10 larvae of S. frugiperdasecond instar and repeated three times. The best control potential was shown by A. muricata 3% extract. Extract A. Muricata 3% can control S. frugiperda with a larval mortality value of 83.33 ± 5.77%, antifeedant activity by 91.11%, and inhibits larval development up to 3.84 days.